Nonclassical Approximate Symmetries of Evolution Equations with a Small Parameter - Kordyukova, S. (Symmetry, Integrability and Geometry: Methods and Applications, 2006)
We introduce a method of approximate nonclassical Lie-Bäcklund symmetries for partial differential equations with a small parameter and discuss applications of this method to finding of approximate solutions both integrable and nonintegrable equations.